IMITATING NEUTRON IRRADIATION DAMAGE USING A COMBINATION OF ION BEAMS - Václav Šísl; Martin Ševeček (Acta Polytechnica CTU Proceedings, 2018)
There is a strong motivation for using ion beams to imitate neutron irradiation damage, mainly in order to reduce costs and time demands linked to neutron irradiation experiments. The long-term goal of the authors is to create an ion irradiation methodology, which could be employed in the development process of innovative nuclear fuel materials. This methodology will be based on combining of a set of ion beams in such a way that the final distribution of irradiation-induced defects in the material structure is similar to the one which would have been introduced by neutrons in a nuclear reactor. The first part of the methodology is represented by an optimization tool described here. The tool uses a third party Monte Carlo code SRIM to simulate ion transport in a target and to determine the distribution of radiation damage. Subsequently, a custom genetic optimization algorithm is applied to a set of damage distribution profiles to find their optimal combination.